Adaptive Market Hypothesis: Evidence from the Ghanaian Stock Market. Issue 2 (3rd April 2018) - Numapau Gyamfi, Emmanuel
ABSTRACT: This study examines the return predictability of two indices – the GSEALSH index and the GSEFSII index on the Ghana stock market. We compare results from analyzing the return series between January 4, 2011 and August 28, 2015 using the generalized spectral test, the automatic portmanteau Box-Pierce test and the wild-bootstrapped automatic variance ratio test. A rolling window approach is used to track whether returns are predictable or not through time. It was observed that the GSEALSH index was more highly predictable than the GSEFSII index in all the three tests. The results obtained are consistent with the Adaptive Market Hypothesis.